Vav family exchange factors: an integrated regulatory and functional view - Bustelo, Xosé R (Small GTPases, 2014)
The Vav family is a group of tyrosine phosphorylation-regulated signal transduction molecules hierarchically located downstream of protein tyrosine kinases. The main function of these proteins is to work as guanosine nucleotide exchange factors (GEFs) for members of the Rho GTPase family. In addition, they can exhibit a variety of catalysis-independent roles in specific signaling contexts. Vav proteins play essential signaling roles for both the development and/or effector functions of a large variety of cell lineages, including those belonging to the immune, nervous, and cardiovascular systems. They also contribute to pathological states such as cancer, immune-related dysfunctions, and atherosclerosis. Here, I will provide an integrated view about the evolution, regulation, and effector properties of these signaling molecules. In addition, I will discuss the pros and cons for their potential consideration as therapeutic targets.